El Excentrico, 1954-12-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
December 20, 1954 [20 de diciembre de 1954]. Ano 5, No.4. Cover contains a Christmas-themed greeting card. Headline reads, "Greetings from El Excentrico's Staff and our Friendly Sponsors."